Paganini's daemon a most enduring legend - Kremer, Gidon 1947-; Nupen, Christopher; Williams, John 1941-; Foster, Lawrence 1941-; Paganini, Nicolò 1782-1840
This is a Christopher Nupen film about the most charismatic performer in the entire history of Western classical music, also the most talked about, the most controversial, the most famous and the most successful classical soloist that the world of music has ever known. While being hailed as the greatest performing musician of his time, Paganini was denounced again and again by knowledgeable critics as a charlatan, in league with the devil, and an avaricious man with scant respect for those who responded so enthusiastically to his unforgettable gift
Title from resource description page (viewed July 25, 2014)
Keywords: Violinists; Violinists -- Italy -- Biography; documentaries; Paganini, Nicolò / 1782-1840; Italy; Streaming videos; Biographies; Documentary films